Hebrew lexical semantics and daily life in ancient Israel : what's cooking in biblical Hebrew? - Peters, Kurtis. (Biblical Interpretation Series, 2016)
In Hebrew Lexical Semantics and Daily Life in Ancient Israel , Kurtis Peters hitches the world of Biblical Studies to that of modern linguistic research. Often the insights of linguistics do not appear in the study of Biblical Hebrew, and if they do, the theory remains esoteric. Peters finds a way to maintain linguistic integrity and yet simplify cognitive linguistic methods to provide non-specialists an access point. By employing a cognitive approach one can coordinate the world of the biblical text with the world of its surroundings. The language of cooking affords such a possibility - Peters evaluates not only the words or lexemes related to cooking in the Hebrew Bible, but also the world of cooking as excavated by archaeology.